1997
DOI: 10.1099/00221287-143-4-1423
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genetic diversity of nonecapsulated Haemophilus influenzae from various diseases

Abstract: Genetic relationships among 80 isolates of nonencapsulated Haemophilus influenzae recovered from different disease types were determined by multilocus enzyme electrophoresis (MEE) a t 13 enzyme loci in an attempt to assess the association between multilocus genotype and disease. The isolates were obtained from 15 patients with meningitis, 10 with otitis media, I 9 with chronic bronchitis, 20 with cystic fibrosis, and 16 were obtained from healthy carriers. The 80 isolates were assigned to 69 electrophoretic ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…As it is suggested that NTHi isolates from acute infections are more diverse than either carrier or chronic respiratory infection isolates [5], it was of interest to determine if the heterogeneity in P5 from various anatomical sites represented the same diversity. The hypervariable regions in this analysis occur predominantly in three regions, which correspond to the first three surfaceexposed loops, similar to the hypervariable regions identified by Duim et al [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it is suggested that NTHi isolates from acute infections are more diverse than either carrier or chronic respiratory infection isolates [5], it was of interest to determine if the heterogeneity in P5 from various anatomical sites represented the same diversity. The hypervariable regions in this analysis occur predominantly in three regions, which correspond to the first three surfaceexposed loops, similar to the hypervariable regions identified by Duim et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…This includes chaperones and outer-membrane ushers that form anchor proteins which connect the fimbriae to the cell [31]. The genomic organisation of the p. 5 gene does not suggest that same organisation seen with other fimbrial operons, at least in the Rd strain [20]. However, the possibility that P5 plays some role in the biogenesis of fimbriae cannot be excluded and may help explain some of the anomalies associated with the lack of fimbriae in the P5 mutant strain [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…outermembrane protein typing, MLEE, PFGE, RAPD or multilocus sequence typing, have been used to evaluate NTHI strain relationships (Fuste et al, 1996;Gazagne et al, 1998;Gilsdorf, 1998;Moor et al, 1999;Saito et al, 1999;St Geme et al, 1994;van Belkum et al, 1994van Belkum et al, , 1997. Of these, some were aimed at finding differences among NTHI strains isolated from patients with persistent infections and from healthy humans (Cerquetti et al, 2000;van Alphen et al, 1991van Alphen et al, , 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with encapsulated strains, non-encapsulated H. influenzae are less well characterized and are thought to be more diverse (Fuste et al, 1996). Most studies directed towards recognizing links between closely related but not identical NTHI strains have been conducted by application (Fuste et al, 1996;Jordens et al, 1993;van Alphen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%